Low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent, preparation method and application thereof

By synthesizing and dispersing hydrophobic polymer nanoparticles in a low eutectic solvent to form a composite well wall reinforcement, the problem of well wall instability of water-based drilling fluid when drilling mud shale is solved, and efficient and environmentally friendly drilling effect is achieved.

CN119775493APending Publication Date: 2025-04-08SINOPEC OILFIELD SERVICE CORPORATION +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411937483.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing water-based drilling fluid often has the problem of well wall instability when drilling mud shale. The inhibition effect of the existing technology is not ideal and has a large pollution to the oil layer. The environmental friendliness and efficiency of nanosealers are insufficient.

Method used

The composite well wall reinforcement agent of eutectic solvent-hydrophobic polymer nanoparticles are used to mediate the in-situ synthesis of hydrophobic polymer nanoparticles in the eutectic solvent through cyclodextrin, and uniformly disperse them in the eutectic solvent to form a composite well wall reinforcement agent to reduce the ionic activity of water-based drilling fluid, improve the stability of the drilling fluid, and seal the tiny cracks in mud shale.

Benefits of technology

It effectively reduces the ionic activity of water-based drilling fluid, improves the stability of drilling fluid, strengthens the well wall, avoids the instability of the well wall caused by crack expansion, and reduces pollution to the oil layer, achieving environmentally friendly and efficient drilling effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener, a preparation method and application thereof, and the preparation steps are as follows: first, a hydrogen bond acceptor and a hydrogen bond donor are mixed and stirred at a certain temperature to form a low eutectic solvent; then, cyclodextrin is mixed with an organic hydrophobic monomer and ground by wetting with an appropriate amount of water to obtain a hydrophobic monomer / cyclodextrin host-guest complex; then, the hydrophobic monomer / cyclodextrin host-guest complex and an initiator are added to the low eutectic solvent, stirred and heated, and the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener is obtained after cooling to room temperature. The low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener of the present invention can reduce the ion activity of water-based drilling fluid, improve the stability of drilling fluid, and introduce hydrophobic polymer nanoparticles to plug tiny nanocracks in mud shale, strengthen the well wall, and avoid the expansion of cracks leading to well wall instability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener, further relates to a preparation method of the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener, and relates to the application of the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener, belonging to the technical field of well wall strengthening materials. Background Art

[0002] There are three ways to solve the instability of shale: inhibition, sealing and mechanical balance.

[0003] At present, the inhibition of drilling fluids at home and abroad is mainly achieved by reducing ion activity using organic salts, inorganic salts and non-salts. For example: organic amines, potassium ions, polyaluminum, etc., but during field application, these materials often have problems such as difficult to control drilling fluid performance and unsatisfactory inhibition effects. In addition, it will cause pollution to the oil layer. With the improvement of environmental awareness and the development of environmental protection policies, while taking into account economic benefits, the necessity of optimizing high-performance water-based drilling fluids is increasing day by day. In order to effectively solve the problem of wellbore instability of water-based drilling fluids and improve construction quality, it is urgent to develop a more environmentally friendly and low-cost high-performance water-based drilling fluid wellbore strengthener. The drilling fluid system with low activity and high-efficiency plugging performance is a strong help to the smooth exploitation of shale gas. During the drilling process, it can effectively prevent solid particles and filtrate from entering the formation and prevent them from damaging the formation.

[0004] Low eutectic solvents have good wettability and low interfacial tension, and can promote the formation of dense and uniform mud cakes on the wellbore wall. This mud cake can effectively isolate the invasion of formation fluids, effectively reduce the filtration loss of mud, and reduce the instability of the wellbore wall. After the low eutectic solvent is dissolved in water, it will dissociate ions with a large number of hydrogen bond donors and acceptors. The water around these ions will gather, and the free water in the solution will decrease accordingly, that is, the water activity will decrease, thereby inhibiting the hydration of clay and rock on the wellbore wall. The cationic amines and polyhydroxy structures in the low eutectic solvent system provide multiple adsorption sites, which can adhere to the pores of the wellbore wall through electrostatic and hydrogen bonding, thereby achieving effective plugging of microcracks, but the strength and hardness of the low eutectic solvent are often difficult to meet the requirements.

[0005] The Chinese invention patent with the announcement number CN 116064001B discloses a water-based drilling fluid for strengthening the well wall in shale formations. Its shortcomings are as follows: 1. Styrene, butyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid, initiator, cationic structure agent and cross-linking agent are used together to enable the wall protector to form a protective film on the well wall; the protective film is hard and brittle and is easy to break under certain conditions, and cannot fully cover the mud shale on the well wall. 2. Although micron and nano-level rigid particles are added, they cannot be well dispersed in the drilling fluid, so the nano-voids that can be blocked are limited. 3. Nano-micron activity inhibitors are ethylene glycol, propylene glycol, glycerol, potassium chloride, sodium formate, potassium formate and cesium formate, which are non-salts, inorganic salts and organic salts respectively. Inorganic salts are the most commonly used activity regulators, which are highly efficient and low in cost, but have a great impact on drilling fluids and cause great pollution to the surrounding environment; organic salt reagents have a relatively lower efficiency than inorganic salts, but most of them are environmentally friendly and have low toxicity, and some are biodegradable; the advantages of non-salts are good environmental protection, non-toxic, harmless and degradable, but the activation efficiency is low.

[0006] The Chinese invention patent with the announcement number CN 114621737B discloses a water-based drilling fluid system, which has the following defects: although the nano-graphene surface-modified with polyethylene glycol used as the nano-blocking agent has high strength and hardness and good water solubility, the inhibitor aromatic amine hydrochloride used with it is often difficult to decompose and will persist in the environment. Once discharged into the environment, they may cause pollution to water bodies, soil and atmosphere. Due to their toxicity, the discharge of aromatic amine compounds is strictly controlled, and effective wastewater treatment measures need to be taken to reduce their impact on the environment. Summary of the invention

[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification of this application and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0009] The primary purpose of the present invention is to overcome the problem in the prior art that wellbore instability accidents often occur when water-based drilling fluid encounters shale, and to provide a low eutectic solvent-hydrophobic polymer nanoparticle composite wellbore strengthener, which can reduce the ion activity of water-based drilling fluid, improve the stability of drilling fluid, and introduce hydrophobic polymer nanoparticles to seal tiny nanocracks in shale, strengthen the wellbore, and prevent the cracks from expanding and causing wellbore instability.

[0010] In order to solve the above technical problems, the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention is characterized in that hydrophobic polymer nanoparticles are in situ synthesized in the low eutectic solvent under the mediation of cyclodextrin and are uniformly dispersed in the low eutectic solvent, and the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 5% to 10% of the mass of the low eutectic solvent; the molecular formula of the hydrophobic polymer nanoparticle is:

[0011]

[0012] Another object of the present invention is to overcome the problems existing in the prior art and provide a method for preparing a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener. The prepared composite well wall strengthener can reduce the ion activity of water-based drilling fluid, improve the stability of drilling fluid, and introduce hydrophobic polymer nanoparticles to seal tiny nanocracks in shale, strengthen the well wall, and prevent the cracks from expanding and causing well wall instability.

[0013] In order to solve the above technical problems, the preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0014] S1, preparing quaternary ammonium salt polymer;

[0015] S2, preparing hydrogen bond acceptors;

[0016] S3, preparing a hydrogen bond donor;

[0017] S4, mixing the hydrogen bond acceptor and the hydrogen bond donor, stirring and heating to generate a deep eutectic solvent;

[0018] S5, mixing cyclodextrin and an organic hydrophobic monomer and grinding them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex;

[0019] S6. Add the hydrophobic monomer / cyclodextrin host-guest complex into a low eutectic solvent, add an initiator and heat under stirring, and obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener after cooling to room temperature.

[0020] Furthermore, the specific preparation process of the quaternary ammonium salt polymer in step S1 is as follows: first, choline chloride and acryloyl chloride are mixed and stirred in a molar ratio of 1:1 in an ice bath for more than 10 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, and potassium persulfate is used as an initiator to mix and stir the reaction at 70±3°C for 4 to 6 hours to generate a quaternary ammonium salt polymer.

[0021] Furthermore, in step S2: choline chloride or tetramethylammonium chloride or trimethylphenylammonium chloride is mixed and stirred with the quaternary ammonium salt polymer for more than 1 hour to generate a mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt as the hydrogen bond acceptor.

[0022] Furthermore, in step S3: the small molecule alcohol and the macromolecular alcohol are mixed and stirred for more than half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as the hydrogen bond donor; the small molecule alcohol is ethylene glycol and / or ethanol, and the macromolecular alcohol is polyvinyl alcohol.

[0023] Further, in step S4: the mixture of the small molecule quaternary ammonium salt + the macromolecular quaternary ammonium salt and the mixture of the small molecule alcohol + the macromolecular alcohol are mixed and stirred at 70±3° C. for more than 40 minutes to generate the low eutectic solvent.

[0024] Further, in step S5: the organic hydrophobic monomer is styrene or butyl acrylate, and the cyclodextrin is α-cyclodextrin;

[0025] Or the organic hydrophobic monomer is N-naphthyl acrylamide, and the cyclodextrin is β-cyclodextrin.

[0026] Furthermore, in step S6: the mass of the hydrophobic monomer / cyclodextrin host-guest complex is 5-10% of the mass of the low eutectic solvent, and the initiator is potassium persulfate and its mass is 0.5% of the mass of the organic hydrophobic monomer; stirring at 60-80° C. for 4-6 hours, and constructing a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener by in-situ synthesis in the low eutectic solvent mediated by cyclodextrin.

[0027] Furthermore, in step S1, during the synthesis of the quaternary ammonium salt polymer, the molar ratio of the copolymerization of the quaternary ammonium salt monomer and acrylic acid is 9:(1-6).

[0028] Furthermore, in the hydrogen bond acceptor, small molecule quaternary ammonium salt accounts for 70% to 90% by weight.

[0029] Furthermore, in the hydrogen bond donor, small molecule alcohol accounts for 70% to 90% by weight.

[0030] Furthermore, the molar ratio of the organic hydrophobic monomer to cyclodextrin is (0.5-1):1, and the initiator is potassium persulfate and its mass is 0.5-1% of the mass of the organic hydrophobic monomer.

[0031] Further, the molecular formula of the quaternary ammonium salt monomer is:

[0032]

[0033] The reaction process for generating quaternary ammonium salt monomer is as follows:

[0034]

[0035] Further, the molecular formula of the quaternary ammonium salt polymer is:

[0036]

[0037] The polymerization process of the quaternary ammonium salt polymer is as follows:

[0038]

[0039] Further, the N-naphthyl acrylamide hydrophobic monomer is obtained by reacting acryloyl chloride with naphthylamine under ice bath conditions, and the process is as follows:

[0040]

[0041] Further, in step S6, the N-naphthyl acrylamide hydrophobic monomer / β-cyclodextrin host-guest complex is polymerized in a low eutectic solvent at 70±3° C. and stirred for 4 to 6 hours under the action of potassium persulfate initiator, and the generated hydrophobic polymer nanoparticles have the following molecular formula:

[0042]

[0043] Another object of the present invention is to overcome the problems existing in the prior art and provide an application of a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener, which is used in water-based drilling fluids for shale wells to reduce the ion activity of the water-based drilling fluids and improve the stability of the drilling fluids. Hydrophobic polymer nanoparticles are introduced to seal tiny nanocracks in the shale, strengthen the well wall, and prevent the cracks from expanding and causing well wall instability.

[0044] In order to solve the above technical problems, the application of the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener of the present invention is characterized in that when used for underground leak plugging, the above-mentioned low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener is added to the water-based drilling fluid, and the amount of the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener accounts for 3-6%wt of the water-based drilling fluid.

[0045] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The advantage of using macromolecules + small molecules as hydrogen bond donors and acceptors is that the small molecules have strong mobility and can be dispersed into the gaps between clay layers to prevent water molecules from penetrating; the macromolecules have large molecular weights and long molecular chains, which can glue the clay together, enhance its stability, and the hydrophobic groups in their structure can reduce the hydrophobicity of the clay. At the same time, the hydroxyl groups and highly electronegative atoms in the structure of the low eutectic solvent can form hydrogen bonds with water molecules and aggregate the solute molecules in the aqueous solution through hydrogen bonds to reduce the water activity. Therefore, the hydration of clay and rock on the well wall can be better inhibited during the drilling process.

[0046] 2. Simply adding a low eutectic solvent to a water-based drilling fluid often makes it difficult to meet the required strength and hardness. Nanoparticles often have strong hardness and good high temperature resistance. However, a single nanomaterial is often not easy to be retained in microcracks during the drilling process and cannot play a good bridging role. The present invention introduces nanoparticles into the low eutectic solvent to make up for the defects of the low eutectic solvent and nanomaterials. During the oil field drilling process, the low eutectic solvent adheres to the pores of the well wall through electrostatic action and hydrogen bonding, thereby achieving effective plugging of microcracks, improving the plugging performance of the drilling fluid, strengthening the well wall, avoiding the development of small cracks into large-size cracks, and preventing the well wall from becoming unstable.

[0047] 3. Most nanoparticles have hydrophobic properties and are difficult to achieve good dissolution and dispersion in polar low eutectic solvents. Therefore, nanoparticles cannot usually be directly reacted and generated stably in low eutectic solvents. The present invention introduces cyclodextrin molecules to mediate organic hydrophobic monomers such as styrene, acrylate, N-naphthyl acrylamide and cyclodextrin molecules to form a host / guest supramolecular complex. Since the outer edge of cyclodextrin is hydrophilic and the inner cavity is hydrophobic, it can provide a hydrophobic binding site like an enzyme, as a main body to encapsulate various appropriate guests, such as organic molecules, inorganic ions and gas molecules, etc. The large number of hydroxyl groups on its outer surface can also make it well dissolved and dispersed in polar solvents, so as to dissolve in polar low eutectic solvents, and then carry out a polymer reaction under the action of an initiator to produce high molecular nanoparticles. Through this polymerization reaction of nanoparticles mediated by cyclodextrin in a low eutectic solvent, the preparation of low eutectic solvents, the preparation of nanoparticles and the compounding of the two can be completed in one step. The prepared nanoparticles have uniform size and good dispersion stability in the system, which is conducive to the good synergy between the nanoparticles and the low eutectic solvent, and plays a synergistic role in the drilling fluid system.

[0048] 4. The composite well wall strengthening agent of the present invention is applied to water-based drilling fluid. When the input ratio is 5%wt, the shale rolling recovery rate reaches more than 94%, and the shale expansion rate is less than 7.5%. It can effectively inhibit the hydration and expansion of mud shale, thereby reducing the occurrence of complex situations such as well wall collapse and stuck drill. The medium-pressure filtration loss after aging is less than 2.7mL, and the medium-pressure filtration loss after aging with the addition of poly-N-naphthyl acrylamide nanoparticles reaches 1.3ml and 1.4ml, which is easy to form a low-permeability, flexible, thin and dense filter cake, which is conducive to stabilizing the well wall and protecting the oil and gas layer. Pressurized to 0.69MPa, the depth of the drilling fluid immersed in the sand bed after 10min is 0.5-1.4cm, which is very effective in plugging formation cracks and pores. DETAILED DESCRIPTION

[0049] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0051] Example 1

[0052] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0053] S1. Preparation of quaternary ammonium salt polymer

[0054] First, choline chloride and acryloyl chloride were mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer. The reaction process is as follows:

[0055]

[0056] The generated quaternary ammonium salt monomer is then copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to the acrylic acid is 9:1, potassium persulfate is used as an initiator, and the mixture is stirred and reacted at 67°C for 4 hours to generate a quaternary ammonium salt polymer. The polymerization process is as follows:

[0057]

[0058] S2. Preparation of hydrogen bond acceptors

[0059] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% by weight.

[0060] S3. Preparation of hydrogen bond donors

[0061] Ethylene glycol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 70%wt.

[0062] S4. Preparation of deep eutectic solvent

[0063] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 67° C. for 40 minutes to generate a low eutectic solvent.

[0064] S5. Mix α-cyclodextrin and the organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.5:1.

[0065] S6. Adding the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 5% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.5% of the mass of the organic hydrophobic monomer; stirring at 60° C. for 4 hours, and synthesizing the hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0066] The polymerization process of styrene is as follows:

[0067] After cooling to room temperature, a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent is obtained.

[0068] Example 2

[0069] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0070] S1. Preparation of quaternary ammonium salt polymer

[0071] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 11 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:3, and potassium persulfate is used as an initiator to mix and stir at 70°C for 5 hours to generate a quaternary ammonium salt polymer.

[0072] S2. Preparation of hydrogen bond acceptors

[0073] Tetramethylammonium chloride and quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80%wt.

[0074] S3. Preparation of hydrogen bond donors

[0075] The ethanol and polyvinyl alcohol were mixed and stirred for 35 minutes to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounted for 80% wt.

[0076] S4. Preparation of deep eutectic solvent

[0077] A mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt and a mixture of small molecule alcohol + large molecule alcohol are mixed and stirred at 70° C. for 40 minutes to generate a low eutectic solvent.

[0078] S5. Mix α-cyclodextrin and the organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.7:1.

[0079] S6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 7% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.7% of the mass of the organic hydrophobic monomer; stir at 70°C for 5 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and cool to room temperature to obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener.

[0080] Example 3

[0081] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0082] S1. Preparation of quaternary ammonium salt polymer

[0083] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 11 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:6, and potassium persulfate is used as an initiator to mix and stir at 73°C for 6 hours to generate a quaternary ammonium salt polymer.

[0084] S2. Preparation of hydrogen bond acceptors

[0085] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 90% by weight.

[0086] S3. Preparation of hydrogen bond donors

[0087] The ethanol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 90% by weight.

[0088] S4. Preparation of deep eutectic solvent

[0089] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 73° C. for 45 minutes to generate a low eutectic solvent.

[0090] S5. Mix α-cyclodextrin and the organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0091] S6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 10% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 1% of the mass of the organic hydrophobic monomer; stir at 80°C for 6 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and cool to room temperature to obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener.

[0092] Example 4

[0093] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0094] S1. Preparation of quaternary ammonium salt polymer

[0095] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:4, and potassium persulfate is used as an initiator to mix and stir at 70°C for 5 hours to generate a quaternary ammonium salt polymer.

[0096] S2. Preparation of hydrogen bond acceptors

[0097] The trimethylphenylammonium chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80% by weight.

[0098] S3. Preparation of hydrogen bond donors

[0099] Ethylene glycol and polyvinyl alcohol were mixed and stirred for 35 minutes to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounted for 80%wt.

[0100] S4. Preparation of deep eutectic solvent

[0101] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 70° C. for 45 minutes to generate a low eutectic solvent.

[0102] S5. Mix β-cyclodextrin and organic hydrophobic monomer N-naphthyl acrylamide and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.8:1.

[0103] N-naphthyl acrylamide is obtained by reacting acryloyl chloride with naphthylamine in an ice bath, and the process is as follows:

[0104]

[0105] S6, adding the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 10% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.8% of the mass of the organic hydrophobic monomer; stirring at 80° C. for 6 hours, and synthesizing the hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0106] The polymerization process of N-naphthyl acrylamide is as follows:

[0107] After cooling to room temperature, a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent is obtained.

[0108] Example 5

[0109] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0110] S1. Preparation of quaternary ammonium salt polymer

[0111] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:5, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0112] S2. Preparation of hydrogen bond acceptors

[0113] Tetramethylammonium chloride and quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80%wt.

[0114] S3. Preparation of hydrogen bond donors

[0115] Ethylene glycol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 80%wt.

[0116] S4. Preparation of deep eutectic solvent

[0117] A mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt and a mixture of small molecule alcohol + large molecule alcohol are mixed and stirred at 70° C. for 40 minutes to generate a low eutectic solvent.

[0118] S5. Mix α-cyclodextrin and organic hydrophobic monomer butyl acrylate and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0119] S6. Adding the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 8% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.8% of the mass of the organic hydrophobic monomer; stirring at 70° C. for 5 hours, and synthesizing the hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0120] The polymerization process of butyl acrylate is as follows:

[0121] After cooling to room temperature, a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent is obtained.

[0122] Example 6

[0123] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0124] S1. Preparation of quaternary ammonium salt polymer

[0125] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:2, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0126] S2. Preparation of hydrogen bond acceptors

[0127] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% by weight.

[0128] S3. Preparation of hydrogen bond donors

[0129] Ethylene glycol and ethanol are mixed in a molar ratio of 1:1, and then mixed with polyvinyl alcohol for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 90%wt.

[0130] S4. Preparation of deep eutectic solvent

[0131] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 71° C. for 40 minutes to generate a low eutectic solvent.

[0132] S5. Mix α-cyclodextrin and the organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.9:1.

[0133] S6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 6% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.6% of the mass of the organic hydrophobic monomer; stir at 70°C for 5 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and cool to room temperature to obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall enhancer.

[0134] Example 7

[0135] The preparation method of the deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent of the present invention comprises the following steps in sequence:

[0136] S1. Preparation of quaternary ammonium salt polymer

[0137] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:5, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0138] S2. Preparation of hydrogen bond acceptors

[0139] The trimethylphenylammonium chloride and the quaternary ammonium salt polymer are mixed and stirred for 1.5 hours to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 90% by weight.

[0140] S3. Preparation of hydrogen bond donors

[0141] Ethylene glycol and ethanol are mixed in a molar ratio of 1:1, and then mixed with polyvinyl alcohol for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 80%wt.

[0142] S4. Preparation of deep eutectic solvent

[0143] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 70° C. for 45 minutes to generate a low eutectic solvent.

[0144] S5. Mix β-cyclodextrin and organic hydrophobic monomer N-naphthyl acrylamide and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0145] S6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 9% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.9% of the mass of the organic hydrophobic monomer; stir at 80°C for 6 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and cool to room temperature to obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener.

[0146] The performance tests of each embodiment are as follows:

[0147] 1. Shale rolling recovery test

[0148] Base slurry: 5% bentonite + 1% lignite resin SPNH, 5‰ sulfomethylphenolic resin type I SMP-1, 3‰ polyacrylate, 2‰ polyanionic cellulose PAC (600g bentonite + 12L clean water), about 1 part per ten thousand caustic soda can be added to adjust the pH value to 9, and sealed and cured at room temperature for 24 hours.

[0149] Comparative Example 1: The difference from the preparation method of Example 1 is that choline chloride and the synthetic quaternary ammonium salt polymer are mixed and stirred, with choline chloride accounting for 60%; ethylene glycol and polyvinyl alcohol are mixed and stirred, with ethylene glycol accounting for 60%.

[0150] Comparative Example 2: The difference from the preparation method of Example 1 is that: small molecule quaternary ammonium salt is mixed with large molecule quaternary ammonium salt, and the small molecule quaternary ammonium salt accounts for 95%; small molecule alcohol is mixed with large molecule alcohol, and the small molecule alcohol accounts for 95%.

[0151] Comparative Example 1, Comparative Example 2 and Examples 1 to 7 were added to the above base slurry to prepare a water-based drilling fluid for testing, with the addition ratio being 5%wt, the same below.

[0152] The test was conducted in accordance with Chapter 6 of the industry standard SY / T 5613-2016 "Test Methods for Physical and Chemical Properties of Shale by Drilling Fluids". The cuttings mass m1 before rolling is 50g, the screen residue mass m2 after rolling and the rolling recovery rate are shown in Table 1:

[0153] Table 1

[0154] sample <![CDATA[m2 / g]]> Rolling recovery rate (%) Base slurry 23.6 47.2 Comparative Example 1 40.03 80.06 Comparative Example 2 45.96 91.92 Example 1 47.38 94.76 Example 2 47.54 95.08 Example 3 49.02 98.04 Example 4 48.16 96.32 Example 5 47.85 95.7 Example 6 47.65 95.3 Example 7 48.41 96.82

[0155] Rolling recovery rate is an important indicator to measure the ability of drilling fluid to inhibit hydration and expansion of shale. During the drilling process, a high rolling recovery rate usually means that the drilling fluid can effectively inhibit the hydration and expansion of shale, thereby reducing the occurrence of complex situations such as wellbore collapse and drill sticking, and ensuring the smooth progress of drilling operations.

[0156] It can be seen from Table 1 that the low eutectic solvent has a great influence on the shale rolling recovery rate. The low eutectic solvent configured in the present invention is composed of a macromolecule plus a small molecule as a hydrogen bond donor and acceptor. The content of small molecules plays a major role in the shale rolling recovery rate, but if there are only small molecules to prevent water molecules from penetrating without the hydrophobic groups of large molecules, the effect will be reduced. The rolling recovery rates in the embodiments of the present invention have reached more than 94%, and the highest can reach 98.04%. However, after the small molecule content of Comparative Example 1 was adjusted to 60%, its shale rolling recovery rate dropped greatly to only 80%. When the small molecule content of Comparative Example 2 was adjusted to 95%, it would still drop to 91%. However, compared with Comparative Example 1, it is still higher.

[0157] 2. Shale expansion rate test

[0158] The above-mentioned base slurry, comparative example 1 and comparative example 2 are still used.

[0159] The test was conducted in accordance with Chapter 5 of the industry standard SY / T 5613-2016 "Test Methods for Physical and Chemical Properties of Shale by Drilling Fluids". The test results after 2 hours and 16 hours are shown in Table 2:

[0160] Table 2

[0161] %(2h) %(16h) Base slurry 9.61 13.72 Comparative Example 1 5.88 11.4 Comparative Example 2 5.16 10.27 Example 1 3.92 7.31 Example 2 3.61 6.85 Example 3 2.32 4.55 Example 4 2.97 5.12 Example 5 3.02 5.54 Example 6 3.31 6.13 Example 7 2.67 4.87

[0162] The shale expansion rate is an important parameter to measure the volume expansion of shale after it comes into contact with water. It is of great significance for the exploration and development of oil and gas, as well as the design and optimization of drilling fluids. Generally speaking, a lower expansion rate means that the volume of shale changes less after it comes into contact with water, which may be beneficial to maintain the stability of the formation, reduce the complexity of the drilling process, and prevent well wall collapse or drill stuck.

[0163] It can be seen from Table 2 that the trends of shale expansion rate and shale rolling recovery rate are consistent. Both of them first improve with the increase of small molecule content. However, if there is no certain amount of macromolecular chain to cooperate, the performance will still decline if the content of small molecules is increased. In the embodiment of the present invention, the shale expansion rate can reach 4.87% even after 16 hours. The small molecule content of comparative example 1 is the lowest, and the small molecule content of comparative example 2 is the highest. However, the shale expansion rates of both are not low, so the proportion of small molecules can only be within a certain range.

[0164] 3. Medium pressure filtration test

[0165] Base slurry is the same as before;

[0166] Comparative Example 3: The only difference between the preparation method of Example 1 and that of Example 1 is that the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 3% of the mass of the deep eutectic solvent.

[0167] Comparative Example 4: The only difference from the preparation method of Example 1 is that the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 13% of the mass of the deep eutectic solvent.

[0168] The samples before and after aging were subjected to medium-pressure filtration test. The sample aging was performed by rolling the sample for 10 hours at 120°C and then cooling it to room temperature. The test was performed in accordance with the "Filtration" chapter standard in API RP 13B-1 "Recommended Practice for Field Testing Water-based Drilling Fluids". The test results are shown in Table 3:

[0169] Table 3

[0170]

[0171] Medium pressure filtration loss is an important indicator of drilling fluid performance. It reflects the volume of drilling fluid passing through a specific filter paper under certain pressure and time conditions. It is usually used to evaluate the filtration characteristics of drilling fluid and the quality of mud cake formed. Generally speaking, the smaller the filtration loss of drilling fluid, the easier it is to form a low-permeability, flexible, thin and dense filter cake, which is beneficial to stabilize the well wall and protect the oil and gas layer.

[0172] It can be seen from Table 3 that the amount of medium pressure filtration loss is closely related to the proportion of nanoparticles in the low eutectic solvent. According to the experimental data, we can find that the effect of adding poly-N-naphthyl acrylamide nanoparticles is the best. The medium pressure filtration loss after aging is only 1.3ml and 1.4ml. On the other hand, adding too much or too little nanoparticles will have a bad effect on the medium pressure filtration loss, as shown in Comparative Examples 3 and 4, where the pressure filtration loss is 2.9ml and 3.9ml.

[0173] 4. Plugging performance test

[0174] The above-mentioned base slurry, comparative example 3 and comparative example 4 are still used.

[0175] By measuring the penetration depth of drilling fluid in the sand bed, the effectiveness of the plugging agent in plugging formation cracks and pores can be evaluated. The plugging properties of the base slurry and various drilling fluids were determined according to API specifications using a non-permeability tester (visual sand bed filter loss tester). The test method is as follows: Add sand with a particle size of 10 to 50 mesh to the cylinder of the visual sand bed filter loss tester, compact and flatten it to form a sand bed, then slowly add 500 mL of base slurry or drilling fluid to the cylinder, let it stand for 10 minutes, measure the depth of the base slurry or drilling fluid immersed in the sand bed, then gradually pressurize to 0.69 MPa, and measure the depth of the drilling fluid immersed in the sand bed after 10 minutes. The test results are shown in Table 4.

[0176] Table 4

[0177]

[0178] The results of the plugging performance test and the medium-pressure filtration performance test have the same trend, which is closely related to the proportion of nanoparticles in the drilling fluid. If the proportion of nanoparticles is too high, the results of the medium-pressure filtration test and the plugging performance test will only fluctuate within a certain range. Therefore, too many nanoparticles in the drilling fluid are unnecessary, but the results are not ideal if the number of nanoparticles is small. Among the nanoparticles synthesized in a low eutectic solvent by the mediation of cyclodextrin in the present invention, the strength of the poly N-naphthyl acrylamide nanoparticles is the highest. The penetration depths of Example 4 and Example 7 after pressurization only reached 0.5 cm and 0.6 cm, but the data after adding too many or too few nanoparticles are not ideal, such as Comparative Example 3 and Comparative Example 4 reached 2.1 cm and 1.6 cm.

[0179] The raw materials used in the present invention are widely available and can be industrially produced. At the same time, the reagents used in the embodiments are all commercially available. The above is only a preferred embodiment of the present invention, which shows and describes the basic principles, main features and advantages of the present invention, but does not limit the scope of patent protection of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. In addition to the above embodiments, the present invention may also have other embodiments without departing from the spirit and scope of the present invention. The present invention may also have various changes and improvements, and all technical solutions formed by equivalent replacement or equivalent conversion fall within the scope of protection required by the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents. The technical features not described in the present invention can be realized by or using the prior art, and will not be repeated here.

Claims

1. A deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent, characterized in that: Hydrophobic polymer nanoparticles are synthesized in situ in a low eutectic solvent under the mediation of cyclodextrin and are uniformly dispersed in the low eutectic solvent. The mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 5% to 10% of the mass of the low eutectic solvent. The molecular formula of the hydrophobic polymer nanoparticles is:

2. A method for preparing a deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent, characterized in that: The steps are as follows: S1, preparing quaternary ammonium salt polymer; S2, preparing hydrogen bond acceptors; S3, preparing a hydrogen bond donor; S4, mixing the hydrogen bond acceptor and the hydrogen bond donor, stirring and heating to generate a deep eutectic solvent; S5, mixing cyclodextrin and an organic hydrophobic monomer and grinding them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex; S6. Add the hydrophobic monomer / cyclodextrin host-guest complex into a low eutectic solvent, add an initiator and heat under stirring, and obtain a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener after cooling to room temperature.

3. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: The specific preparation process of the quaternary ammonium salt polymer in step S1 is as follows: first, choline chloride and acryloyl chloride are mixed and stirred in a molar ratio of 1:1 in an ice bath for more than 10 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, and potassium persulfate is used as an initiator to mix and stir at 70±3°C for 4 to 6 hours to generate a quaternary ammonium salt polymer.

4. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: In step S2: choline chloride or tetramethylammonium chloride or trimethylphenylammonium chloride is mixed and stirred with the quaternary ammonium salt polymer for more than 1 hour to generate a mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt as the hydrogen bond acceptor.

5. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: In step S3: the small molecule alcohol and the macromolecular alcohol are mixed and stirred for more than half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as the hydrogen bond donor; the small molecule alcohol is ethylene glycol and / or ethanol, and the macromolecular alcohol is polyvinyl alcohol.

6. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 4, characterized in that: In step S4: the mixture of the small molecule quaternary ammonium salt + the macromolecular quaternary ammonium salt and the mixture of the small molecule alcohol + the macromolecular alcohol are mixed and stirred at 70±3° C. for more than 40 minutes to generate the low eutectic solvent.

7. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: In step S5: the organic hydrophobic monomer is styrene or butyl acrylate, and the cyclodextrin is α-cyclodextrin; Or the organic hydrophobic monomer is N-naphthyl acrylamide, and the cyclodextrin is β-cyclodextrin.

8. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: In step S6: the mass of the hydrophobic monomer / cyclodextrin host-guest complex is 5-10% of the mass of the low eutectic solvent, and the initiator is potassium persulfate and its mass is 0.5% of the mass of the organic hydrophobic monomer; stirring at 60-80° C. for 4-6 hours, and constructing a low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener by in-situ synthesis in the low eutectic solvent mediated by cyclodextrin.

9. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 3, characterized in that: In step S1, during the synthesis of the quaternary ammonium salt polymer, the molar ratio of the quaternary ammonium salt monomer to the acrylic acid copolymer is 9:(1-6).

10. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 4, characterized in that: In the hydrogen bond acceptor, small molecule quaternary ammonium salt accounts for 70% to 90% by weight.

11. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 5, characterized in that: Among the hydrogen bond donors, small molecule alcohol accounts for 70% to 90% by weight.

12. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 2, characterized in that: The molar ratio of the organic hydrophobic monomer to cyclodextrin is (0.5-1):1, and the initiator is potassium persulfate and its mass is 0.5-1% of the mass of the organic hydrophobic monomer.

13. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 3, characterized in that: The molecular formula of the quaternary ammonium salt monomer is: The reaction process for generating quaternary ammonium salt monomer is as follows:

14. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 3, characterized in that: The molecular formula of the quaternary ammonium salt polymer is: The polymerization process of the quaternary ammonium salt polymer is as follows:

15. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 7, characterized in that: The N-naphthyl acrylamide hydrophobic monomer is obtained by reacting acryloyl chloride with naphthylamine under ice bath conditions, and the process is as follows:

16. The deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent according to claim 7, characterized in that: In step S6, the N-naphthyl acrylamide hydrophobic monomer / β-cyclodextrin host-guest complex is polymerized in a low eutectic solvent at 70±3° C. with stirring for 4 to 6 hours under the action of potassium persulfate initiator, and the generated hydrophobic polymer nanoparticles have the following molecular formula:

17. An application of a deep eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthening agent, characterized in that: When used for underground plugging, the above-mentioned low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener is added to the water-based drilling fluid, and the amount of the low eutectic solvent-hydrophobic polymer nanoparticle composite well wall strengthener accounts for 3-6%wt of the water-based drilling fluid.

Citation Information

Patent Citations

  • Water-based drilling fluid system and preparation method thereof

    CN114621737B

  • A water-based drilling fluid for strengthening the well wall of shale formations and its application

    CN116064001B